Kolaborasi Lintas Institusi untuk Penguatan Deteksi Dini Stunting berbasis Kearifan Lokal di Desa Simpasai Kabupaten Dompu - Ayatullah; Dwi Amanda; Ananda Kurnia Putri; Astuti; Sita Agustina; Abdul Rahman Manga; Fatma Afrianti Gobel; Nurul Jannah; Wahidah; Jaenab (Universitas Merdeka Surabaya, 2025)
The stunting prevalence in Simpasai Village, Dompu Regency, reaches 28.5%, driven by multidimensional factors such as limited understanding of nutrition, limited access to healthcare, and low income. This Student Creativity Program (Program Kreativitas Mahasiswa/PKM) aims to address these issues through an integrated approach that combines digital technology innovation and the empowerment of local food potential. The implementation method includes two main interventions. First, the introduction and implementation of the